2021
DOI: 10.1186/s12978-020-01057-9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and demographic factors associated with fertility preferences among women of reproductive age in Ghana: evidence from the 2014 Demographic and Health Survey

Abstract: Background Understanding women’s desire to have more children is critical for planning towards future reproductive health behaviour. We examined the association between socio-economic and demographic factors and fertility preferences among women of reproductive age in Ghana. Methods This  study used data from the 2014 Ghana Demographic and Health Survey. The sample consisted of 5389 women of reproductive age. We fitted Binary logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…22e24 In this way, education may serve as a proxy for financial security and personal agency vs physical risks of exposure associated with the ability to work remotely and thereby act as a potential mitigatory factor for the effect of the pandemic. In contrast to our study, other research studies found that the desire for children is generally higher among those of lower educational levels 23 and that women of higher SES had lower net fertility, 22e24 potentially because those of higher SES respond faster to changing family norms. 24 However, these analyses were performed with data collected from a nonpandemic period.…”
Section: Clinical and Research Implicationscontrasting
confidence: 99%
“…22e24 In this way, education may serve as a proxy for financial security and personal agency vs physical risks of exposure associated with the ability to work remotely and thereby act as a potential mitigatory factor for the effect of the pandemic. In contrast to our study, other research studies found that the desire for children is generally higher among those of lower educational levels 23 and that women of higher SES had lower net fertility, 22e24 potentially because those of higher SES respond faster to changing family norms. 24 However, these analyses were performed with data collected from a nonpandemic period.…”
Section: Clinical and Research Implicationscontrasting
confidence: 99%
“…A study that assessed women's preferences for having a child was conducted by B.O. Ahinkorah et al (2021). The researchers concluded that women with high socioeconomic status are less likely to want to have more children.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Caldwell (2005) 30,38,41,60]. However, these results contrast earlier studies on this point that higher education is associated with lesser fertility desire [19,[35][36][37]. The discrepancy might be attributed to the difference in the study population, design, and measurement; meanwhile, further study is required to examine the association between level of education and fertility desire in this population group.…”
Section: Discussionmentioning
confidence: 84%